Effect of Organizational Cultural Differences and Mutual Trust on Contract Management of Nonequity Construction Project Alliances - Yanling Zhao; Yingbin Feng; Chenggang Li (Advances in Civil Engineering)
This study aims to examine the impact of organizational cultural difference and mutual trust on the contract management of nonequity project alliances in the construction industry. A questionnaire survey was conducted to collect the quantitative data for this study. The relationships between the variables were analyzed using hierarchical regression analysis. It was found that the contractual complexity of nonequity project alliances was impacted by the differences in management style, differences in organizational responsiveness, mutual goodwill trust, and mutual competence trust. It was also found that the relationship between differences in organizational responsiveness and contractual complexity was moderated by mutual goodwill trust. The research may provide theoretical basis for the management when making decisions on the selection of project alliance partners and contracts. The findings imply that when the firms seek to form project alliances, they need to recognize the level of organizational cultural differences and then determine the proper contractual complexity of the project alliance. In addition, the establishment of mutual goodwill trust between alliance partners will not only reduce the costs of making contracts but also the costs of implementing the contracts.